Clinical features and epidemiology of spondyloarthritides associated with inflammatory bowel disease - Salvarani, Carlo (The WJG Press and Baishideng, 2009)
Inflammation of axial and/or peripheral joints is one of the most frequent extra-intestinal manifestations complicating the clinical course and therapeutic approach in inflammatory bowel diseases (IBD). The frequency of these complications seems to be similar for both diseases, Crohn’s disease and ulcerative colitis. Arthritis associated with IBD belongs to the category of spondyloarthropathies. Axial involvement ranges from isolated inflammatory back pain to ankylosing spondylitis, whereas peripheral arthritis is noted in pauciarticular and in polyarticular disease. Asymptomatic radiological involvement of the sacroiliac joints is reported to occur in up to 50% of patients. Other musculoskeletal manifestations such as buttock pain, dactylitis, calcaneal enthesitis, and thoracic pain are frequently underdiagnosed and, consequently, are not treated appropriately. Several diagnostic approaches and criteria have been proposed over the past 40 years in an attempt to correctly classify and diagnose such manifestations. The correct recognition of spondylarthropathies needs an integrated multidisciplinary approach in order to identify common therapeutic strategies, especially in the era of the new biologic therapies.